Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and mortality in US adults: results from the NHANES 2011–2018 - Yang, Mengmeng; Zhang, Junwei; Feng, Zhenyu; Wang, Meiling; Feng, Quanguan; Zhang, Runping; Wu, Chuanling; Wu, Tian; Zhang, Genggeng; Niu, Yuanzhi; Dong, Qiuju; Han, Qinghua; et al. (Frontiers in Nutrition, 2025)
BackgroundThe NHHR, which is the ratio of non-high-density lipoprotein cholesterol (non-HDL-C) to high-density lipoprotein cholesterol (HDL-C), has been suggested to have a link to several metabolic diseases and cardiovascular diseases (CVD). However, its association with CVD mortality and all-cause mortality remains uncertain.Methods and resultsAnalyzing HDL-C and non-HDL-C used to calculate NHHR were sourced from the National Health and Nutrition Examination Survey (2011–2018). In this experiment, we utilized subgroup analysis to examine the robustness of the results obtained. This study excluded participants under 20 years of age and those with missing NHHR or mortality data, resulting in a final sample of 20,294 participants. We employed logistic regression models to assess the association between NHHR and all-cause mortality and CVD mortality. The NHHR was categorized into four groups (Q1–Q4) according to their values from small to large. In model 3, considering all covariates, individuals in Q4 of NHHR exhibited a 41% higher CVD mortality compared to Q1 (HR = 1.41, 95% CI 1.14, 1.74). To explore the potential non-linear relationships between NHHR and mortality, restricted cubic spline (RCS) and threshold saturation techniques were used. About NHHR and all-cause mortality, the results indicated an L-shaped association, with a breakpoint (K) at 1.18. To the left of this threshold, a negative association was identified (OR = 0.30, 95% CI 0.13, 0.67). But when NHHR is greater than 1.18, the relationship was positive (HR = 1.12, 95% CI 1.06, 1.18).ConclusionAll in all, maintaining NHHR within an optimal range in adults may help reduce the association connected with both all-cause and CVD mortality.